„Head and shoulders, knees and toes....” Using Songs in English Language Teaching - Szabóné Lang Mária; Orosz Andrea (2002)
This thesis examines what the advantages are of using songs and music in English Language Teaching. I propose that learning English through songs and music are not only interesting and amusing but songs help the students' language development. I demonstrate that by singing songs words are kept in the memory better and students can remember these words for a longer time. In order to give proof to my hypothesisIteach the parts of the body with the help of a song and in another group without song. Then I check the pupils' results in several ways to prove my assumption. Using a student questionnaire,Itry to find out more about the topic and I present how the students express their opinion on learning songs in English lessons.
Keywords: Pedagógusképzés